2020
DOI: 10.26832/24566632.2020.050306
|View full text |Cite
|
Sign up to set email alerts
|

Effects of plant growth regulators on growth, flowering, fruiting and fruit yield of cucumber (Cucumis sativus L.): A review

Abstract: This review provides a comprehensive overview of the basic and applied aspects of different plant growth regulators in the regulation of growth and development of cucumber plants. The study is completely based on the use of secondary sources of data; related journals, government institutes, and relevant reports. Foliar application of PGRs has been shown to change the physiological and developmental processes, including plant vegetative growth, sex expression, yield, and yield components in cucumber. There are … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 25 publications
0
7
0
Order By: Relevance
“…In pedunculated cucurbits such as Cucumis sativus , fruit growth is attained through cell expansion and progressive maturation until ripening, which resembles a sigmoid growth habit [ 44 , 45 , 46 ]. Fruit cell number and size are key limiting factors in determining the fruit size and shape, whereby fruit growth is maintained by an accelerated cell division from 0 to 6 DAA, and, thereafter, an exponential enlargement stage from 6 to 15 DAA [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In pedunculated cucurbits such as Cucumis sativus , fruit growth is attained through cell expansion and progressive maturation until ripening, which resembles a sigmoid growth habit [ 44 , 45 , 46 ]. Fruit cell number and size are key limiting factors in determining the fruit size and shape, whereby fruit growth is maintained by an accelerated cell division from 0 to 6 DAA, and, thereafter, an exponential enlargement stage from 6 to 15 DAA [ 45 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
“…Fruit cell number and size are key limiting factors in determining the fruit size and shape, whereby fruit growth is maintained by an accelerated cell division from 0 to 6 DAA, and, thereafter, an exponential enlargement stage from 6 to 15 DAA [ 45 , 47 ]. Such growth and enlargement are largely controlled by phytohormones such as auxin, gibberellins, cytokinins, abscisic acid and ethylene [ 46 ]. Before anthesis, fruit shape and size are correlated with the shape and size of developing inferior ovaries [ 48 , 49 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Plant growth regulators are among the most important chemicals that affect the flowering time and sex of plants [20,57,58]. The use of naphthalene acetic acid led to a minimum sex ratio, which led to an increase in the female functional organ [59][60][61]. Some studies reported that the increase in cucumber productivity is due to the positive role of NAA, which significantly reduced staminate flowers and increased pistillate flowers in cucumbers [28,60,62,63].…”
Section: Effect Of Potassium Nitrate and Naa On The Flowering Stagementioning
confidence: 99%
“…Similar results also reported by Sidhu et al [12 in Muskmelon and Node number of first female flower Similar results also reported by Chowdhary et al [13] in bottle gourd. Sanjeevan Gosai et al [14] observed that Ethrel was found effective in decreasing the number of male or staminate flowers per vine. Similar results were also observed by Ghani et al [15] in bitter gourd (Momordica charantia).…”
Section: Growth Parametersmentioning
confidence: 99%